Exploring experiences of cancer care in Wales - a thematic analysis of free-text responses to the 2013 Wales Cancer Patient Experience Survey (WCPES). - Bracher, Michael; Corner, Jessica; Wagland, Richard (BMJ Publishing Group, 2016)
Objectives: To provide the first systematic analysis of a national (Wales) sample of free-text comments from cancer patients, to determine emerging themes and insights regarding experiences of cancer care in Wales. Design: Thematic analysis of free-text data from a population-based survey. Setting and Participants: Adult patients with a confirmed cancer diagnosis treated within a three month period during 2012 in the seven Health Boards and one trust providing cancer care in Wales. Main outcome measures: Free-text categorised by theme, coded as positive or negative, with ratios. Overarching themes are identified incorporating comment categories. Methods: 4,672 respondents (of n=7352 survey respondents) provided free-text comments. Data was coded using a multistage approach; (1) coding of comments into general categories (e.g. Nursing, Surgery etc.), (2) coding of sub-categories within main categories (e.g. Nursing Care, Nursing Communication etc.), (3) cross-sectional analysis to identify themes cutting across categories (4) mapping of categories/sub-categories to corresponding closed questions in the WCPES data for comparison. Results: Most free-text respondents (82%, n 3818) provided positive comments about their cancer care, with 49% (n=2313) giving a negative comment (ratio: 0.6:1, negative-to-positive). 3172 respondents (67.9% of free-text respondents) provided a comment mapping to one of four overarching themes: communication (n=1673, 35.8% free-text respondents, a ratio of 1.0:1); waiting during the treatment and/or post-treatment phase (n=923, 19.8%, ratio: 1.5:1); staffing and resource levels (n=671, 14.4% ratio: 5.3:1); speed and quality of diagnostic care (n=374, 8.0%, ratio: 1.5 : 1). Within these areas, constituent sub-themes are discussed. Conclusions: This study presents specific areas of concern for cancer patients, and reveals a number of themes present across the cancer journey. While the majority of comments were positive, analysis reveals concerns shared by significant numbers of respondents. Timely communication can help to manage these anxieties, even where delays or difficulties in treatment may be encountered. Strengths and limitations of the study: • Provides further detail on closed measures in population-based survey. • Indicates area of concern not addressed by closed measures. • Volume of comments and ratios of negative to positive comments in specific areas indicate areas of particular concern.